Kinins - Bader, Michael (De Gruyter, 2012)
This handbook of kinin biology and biochemistry covers the current knowledgeof kinins, a family of peptides involved in numerous physiological and pathophysiological processes. Recent publications have shown that the kinin system is highly relevant in a variety of disease states such as diabetes, multiple sclerosis and traumatic injuries. Furthermore, the first drug targeting system has just been approved for clinical use. The goal of this book is to provide advanced students and researchers a basic understanding of the kinin system and its role within the various organ systems. The authors of.